2003
DOI: 10.1023/a:1024414529666
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An important issue in higher education research is how to keep study progress at a good pace. In this article we will deal with the study progress of first-year students in various courses in Dutch higher education. Why are some courses more effective than others? Do such aspects as the composition of student population and different curricula influence variation in study progress, after controlling for individual factors? Multilevel analysis shows that there is in fact such variation between courses and this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The motivation labelled EINT suggests that some students enrolled in an entrepreneurship course because they were interested in an entrepreneurial career (EINT) and wanted to acquire the knowledge and skills associated with an entrepreneurial career (Beekhoven et al 2003). The rational choice theory explains that students' decision to enrol for a course in entrepreneurship is a rational choice if they wish to pursue an entrepreneurial career and thus supports this finding.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The motivation labelled EINT suggests that some students enrolled in an entrepreneurship course because they were interested in an entrepreneurial career (EINT) and wanted to acquire the knowledge and skills associated with an entrepreneurial career (Beekhoven et al 2003). The rational choice theory explains that students' decision to enrol for a course in entrepreneurship is a rational choice if they wish to pursue an entrepreneurial career and thus supports this finding.…”
Section: Discussionmentioning
confidence: 88%
“…A second theory that attempts to explain student choices is the rational choice theory, which suggests that individuals make rational choices, where in the case of EE, the choice could be based on a rational desire to pursue an entrepreneurial career or alternately on a cost-benefit analysis, the latter referring to the estimated costs and benefits of studying within the environment the student choses (Beekhoven et al 2003).…”
Section: Rational Choice Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In these models, both the individual level, which usually explains the most significant part of the variance, and the level of the degree program, which is typically able to explain much less variation, are considered (Tesfaw & Derebew, 2014;Van den Berg & Hofman, 2005). However, Beekhoven et al (2003) highlighted some program characteristics that are helpful in explaining a larger part of the variation. They found that the most effective programs are those with a high share of enrolled women, who are recognized as performing better at university, and those programs requiring a greater number of study hours per week.…”
Section: Academic Performance Of Freshmen Students: Characteristics A...mentioning
confidence: 99%
“…Thus, it is essential to maintain the progress of students in the higher education institutions at a good peace 3 . These can be attained via monitoring achieving learning outcomes which are the expected performance of the graduates.…”
Section: Introductionmentioning
confidence: 99%